La evolución digital y los cambios organizativos: qué respuestas de la ergonomía? - Sylvain Leduc; Ludovic Ponge (Laboreal, 2018)
In the companies, the Digital Transformation (DT) implies several organizational changes with consequences on effective tasks and working conditions. However, these changes are analyzed under the scope of technology-centered approaches, where the “tool” is considered the main solution to solve all work-related problems or by a human-direct approach focused on quality of life at work. This paper aims to show that the work determinants evolve under the effect of the interactions among several changes related to DT. The findings are based on two field studies about practical ergonomics interventions in two different services companies. The results underline the need to change conventional approaches ruling projects of technological change. This paper proposes alternatives to implement such projects, by considering at the same time project leading, tool designing and change management.